Exile, diplomacy and texts : exchanges between Iberia and the British Isles, 1500-1767 - Sáez Hidalgo, Ana; Cano Echevarría, Berta (Intersections (Boston, Mass.), 2021)
"In Exile, Diplomacy and Texts, Ana Sáez-Hidalgo and Berta Cano-Echevarría offer an interdisciplinary narrative of religious, political, and diplomatic exchanges between early modern Iberia and the British Isles during a period uniquely marked by inconstant alliances and corresponding antagonisms. Such conditions notwithstanding, the essays in this volume challenge conventionally monolithic views of confrontation, providing through fresh examination of exchanges of news, movements and interactions of people, transactions of books and texts, new evidence of trans-national and trans-cultural conversations between British and Irish communities in the Iberian Peninsula, and of Spanish and Portuguese 'others' travelling to Britain and Ireland"--